6+2n=13

Simple and best practice solution for 6+2n=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2n=13 equation:



6+2n=13
We move all terms to the left:
6+2n-(13)=0
We add all the numbers together, and all the variables
2n-7=0
We move all terms containing n to the left, all other terms to the right
2n=7
n=7/2
n=3+1/2

See similar equations:

| f/4+5=2 | | 15x-31-9x+11=180 | | -5+9d+2d=9+12d | | 4x+34+(3x)=90 | | 5a=7=4a | | -6(8v-1)=-8(7v+5)-2 | | –2n–16=4n+8 | | Y=-3/7x+5 | | 4m+20=12m-12 | | 4k^2+6k-15=3 | | p-0.7=163 | | 12x-60+4x+12=180 | | 1/8s=1512= | | 3x²-7x+4=24 | | 1/4x-2=12 | | -3x-8=4x+1 | | -2.x+1.8=3.2 | | 4k^2+6k-18=0 | | -4n+-7=-19 | | 5(11x+10)=55x-3 | | 6(3+6a)-5=-5(4-5a) | | 5x-7=3+1 | | 3x+7=-37-7x | | 12x-60+4x+12=90 | | u/2-8=11 | | 2x+6=22x+2=180 | | 2x+3-12x-8=-15 | | 1/8s=1512 | | 2y-7=y/2+2 | | p-5(5p+2)=-8(-1+3p) | | 3a+6=-3=4 | | 9+2n=-1 |

Equations solver categories